ANALYSIS OF FACTORS AFFECTING CUSTOMER SATISFACTION WITH MS GLOW SKIN CARE IN KOTA TEBING TINGGI - Rahmaniar, Rahmaniar; Nur Ilham, Rico; Sinta, Irada; Laxmi Jamatia , Purna (CV. Radja Publika, 2022)
The research method used is the method of qualitative data and quantitative data. While the data used is primary data. The results of testing the first hypothesis proposed stated thatVariables of Service Quality (X1) have an effectto the Customer Satisfaction variable (Y). The second hypothesis put forward states thatProduct Quality variable (X2) has an effectto the Customer Satisfaction variable (Y)The third hypothesis put forward states thatPromotion variable (X3) has an effectto the Customer Satisfaction variable (Y). The fourth hypothesis put forward states thatService Quality Variable (X1), VariableProduct quality(X2), and Promotion (X3) have a significant effect together (simultaneously) on the Customer Satisfaction Variable (Y). Given the business world that continues to move according to its era, it is far-reaching for entrepreneurs to carry forward to come around consequence superiority and accommodation superiority in promoting the consequences they produce. moreover, patronage actors are compulsory to be accomplished to accommodate each the be in want of of their consumers in progression to be accomplished to outlive in their business. MS phosphorescence kotars Tebing Tinggi is anticipated to come around the superiority of the consequences produced in progression to aggrandizement consumer fulfilment in victimisationing MS phosphorescence consequences